Prospective evaluation of airway management in pediatric out-of-hospital cardiac arrest. (November 2020) - Hansen, Matt; Wang, Henry; Le, Nancy; Lin, Amber; Idris, Ahamed; Kornegay, Joshua; Schmicker, Robert; Daya, Mohamud
Abstract: Objective: The objective of the study was to identify the association between airway management modality and time to the initial dose of epinephrine in pediatric out-of-hospital cardiac arrest (OHCA). Methods: This was a prospective observational study conducted between April 2016 to April 2018. Ten Emergency Medical Services (EMS) agencies in 2 US metropolitan areas, which were part of the Resuscitation Outcomes Consortium research network, participated in the study. We included all EMS-treated OHCA patients less than 18 years of age during the study period. Study outcomes included time to the initial dose of epinephrine, airway management success rates, rescue techniques, and complications (e.g. pneumothorax, pneumonia). Results: The study included a total of 155 patients, 67% were male, and 55% were less than age one. The airway management modality (TI, SGA, BMV) was not associated with the time to the intial dose of epinephrine in the adjusted analysis. Tracheal intubation (TI) was the most common airway management modality (47.1%) followed by bag-mask-ventilation (BMV) (40.7%), and supraglottic airways (SGA) (12.3%). Success was 65.7% for TI and 94.7% for SGA. We found a significant difference in the proportion of initial survivors diagnosed with pneumonia on chest X-ray between those with BMV (1/19) versus TI (13/21) p < 0.001. Conclusions: In this prospective study, the airway management modality was not associated with the time to the initial dose of epinephrine. Unexpectedly, pneumonia was significantly more common among children treated with TI compared to BMV. SGAs had high first-attempt success rates, while intubation success rates were low.